Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Evolution of fine structure and pasting properties in wheat starch during medium-high-temperature Daqu fermentation - Zhenbing Ma; Yuanyuan Tian; Dong Zhao; Lihua Zhao; Jia Zheng; Jian Su; Yanping Lu; Yi Ma (Food Research International, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

All-weather anti-salt solar desalination using a sandwich evaporator with thermal storage and asymmetric wettability - Yimin Qu; Changliang Lu; Ziyue Zhang; Xi Wen; Xuanli Jing; Tiaohong Zhang; Ting Lv; Dajian Huang; Yanping Wang; Xiaohu Qiang (Chemical Engineering Journal, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

AI-driven HVAC control optimisation for enhancing energy efficiency and indoor environmental quality: A review of recent advances and emerging approaches - Christopher Otoo; Tao Lu; Xiaoshu Lü; Haneda Katsuyuki; Yanping Yuan (Building and Environment, 2026)

Folding integrated all-paper photoelectrochemical immunoassay using annealed ZnO for point-of-care detection of ferritin - Yibin Cai; Haining Li; Yanping Chen; Shuyi Lu; Huanhuan Zhu; Dianping Tang; Xiao Han; Shaofeng Lin (Analytica Chimica Acta, 2026)

Fabrication of RuCo bimetallic catalyst enabling efficient hydrogen generation via ammonia borane hydrolysis - Xianyun Liu; Lu Zhao; Han Wu; Linyan Bian; Yanping Fan; Baozhong Liu (Fuel, 2026)

Quantification of sediment redox capacities under different Eh conditions by a modified electrochemical method - Yingxiao Tian; Peng Zhang; Yuxi Lu; Yanping Cui; Jinguang Xiao; Chenglong Yu; Songhu Yuan (Chemical Geology, 2026)

Integrative histological and multi-omics analyses reveal hormone-driven cell regeneration mechanisms during postharvest wound healing in melon - Congcong Wang; Yanping Hu; Baibi Zhu; Jihao Chen; Feng Wang; Shiqi Lu; Min Wang (Postharvest Biology and Technology, 2026)

Explainable daily warning of algal concentration exceedance from SHAP-guided temperature and light thresholds - Dawei Xu; Yanping Hu; Shouye Yang; Lu Wang; Long Wang (Journal of Environmental Chemical Engineering, 2026)

Characteristics of soil organic carbon and its stability under different vegetation types and restoration years in Hongze lake wetland, China - Yanan Bai; Haikun Wu; Huifeng Lu; Yuling Yang; Yanping Wang; Lei Dai; Yuchun Ma; Jinqi Wang; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Dynamic analysis and evaluation of gas explosion risk caused by thermal runaway of lithium-ion batteries - Yanping Zhan; Kaiyu Zou; Xiao Chen; Shouxiang Lu (Process Safety and Environmental Protection, 2026)

Comprehensive analysis of lactones and furanones in baijiu: Identification, quantitation, sensorial contribution and aging-related insights - Hao Huang; Yi Li; Huijing Lan; Jia Zheng; Dong Zhao; Jian Su; Yanping Lu; Shuang Chen; Yan Xu (Food Research International, 2026)

Enhancing wildfire spread scale prediction with explainable AI: a hist gradient boosting and SHAP-based approach - Bin Liao; Tao Zhou; Jiong Yu; Yanping Liu; Tao Zhang; Tiantian Lu (Natural Hazards, 2026)

Safe-critical formation reconfiguration of unmanned surface vehicles using closest collision point measurements - Lu Liu; Jiaxing Zhou; Yanping Xu; Zhouhua Peng (Ocean Engineering, 2026)

Strain-specific impacts of Pichia kudriavzevii on metabolite profiles and microbial community dynamics in Chinese Baijiu fermentation: Integrated metabolomics and metagenomics analysis - Boqin Zhang; Mengbo Wang; Jia Zheng; Chenxi Yu; Chunhui Wei; Junyu Ren; Shouying Sun; Guoming Wang; Jinhua Wang; Yanping Lu; Liangcai Lin; Cuiying Zhang (International Journal of Food Microbiology, 2026)

Integrated morphological, transcriptomic, and metabolomic profiling reveals differential development mechanisms in two weeping forsythia genotypes during tissue culture - Yanxia He; Yanping Zheng; Jiaqi Geng; Yue Wang; Na Qi; Xu Lu; Xiaoxiao Wang; Yongjin Sun; Helong Wen; Xiaoya Liu; Xin Sun; Xianping Wang; et al. (Physiology and Molecular Biology of Plants, 2026)

Pa-miR396 targets PaGRFs to disrupt PaGRF–PaGIF transcriptional activation in Platanus acerifolia leaf development - Yongkang Lu; Yuqing Chen; Dasui Li; Manzhu Bao; Yanping Zhang (Plant Science, 2026)

Balancing Accuracy and Speed: Improved D-FINE for Real-Time Ocean Internal Wave Detection - Lu Yu; Yanping Tian; Jie Chen; Cheng Chi; Tingting Li; Jianwei Li (Journal of Marine Science and Engineering, 2026)
Ocean internal waves (IWs), induced by density stratification and fluid perturbations, are significant oceanic phenomena prevalent across global oceans, profoundly impacting marine environments and engineering safety. Although one-stage object detection models are favored in practical applications due to their efficient inference, they often suffer from insufficient accuracy in IW detection tasks. To address this, we introduce a novel one-stage, anchor-free detection approach based on Transformer for IW detection, proposing a new algorithm named IW-D-FINE, which balances detection accuracy and inference efficiency. On the public SAR dataset, IW-D-FINE achieves an AP@0.5 of 90.5, significantly outperforming existing one-stage methods while maintaining faster inference speeds than mainstream two-stage models. Furthermore, to mitigate the scarcity of internal wave samples, we construct a small-scale IWs dataset, YH3-IW-2025, and validate the algorithm thoroughly on this dataset. Experimental results demonstrate that IW-D-FINE exhibits robust performance under complex background interference, highlighting its application potential and scalability in IW detection tasks.

Hour-level humification of papermaking waste residue to produce honeycomb-like controlled-release fertilizer - Dongqing Cai; Shuang Wang; Linying Wang; Zerong Song; Yanping Zhu; Ziyu You; Jinjing Xu; Yan Wang; Wanji Zhu; Rongjun Zhang; Pan Zhao; Xiaofeng Lu; et al. (Journal of Cleaner Production, 2026)

Preparation of sawdust-based degradable mulch film and nutrient slow-release performance evaluation - Xianghai Kong; Rongxi Hu; Zerong Song; Xinxin Zhai; Ziyu You; Yuhao Wang; Pan Zhao; Xiaofeng Lu; Rongjun Zhang; Yanping Zhu; Dongfang Wang; Dongqing Cai (Journal of Environmental Chemical Engineering, 2026)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Interfacially synergistic Photothermal enhancement for solar evaporation by palygorskite-carbon nanotube/chitosan aerogels - Yimin Qu; Changliang Lu; Gaofeng Zhang; Zhu Hu; Dajian Huang; Xiaohu Qiang; Yanping Wang (Desalination, 2025)

Fabrication of a nonwoven fabric-based multifunctional mulch film with Cr(VI) remediation capacity - Dongqing Cai; Jinjing Xu; Jiangshan Li; Xianghai Kong; Maowei Wu; Yan Wang; Wanji Zhu; Pan Zhao; Xiaofeng Lu; Xiaoli Tang; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2025)

Mechanistic insights into co-culture inhibition of pellicle formation in fermented chili peppers by Pediococcus ethanolidurans M1117 - Yumeng Li; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Baiyi Lu; Hong Gao (International Journal of Food Microbiology, 2025)

Naringenin attenuates Mandarin fish ranavirus (MRV)-induced hyperinflammation through the inhibition of MAPK and NF-κB signaling pathways - Ziye Zhang; Yanping Ma; Xinru Gao; Chaojiao Hu; Le Hao; Huijie Lu; Yugu Li; Zhenxing Liu (Fish & Shellfish Immunology, 2025)

Treating waste with waste: 1 h deep-drying of sewage sludge by secondary aluminum ash - Xianghai Kong; Zerong Song; Jie Wu; Ziyu You; Xiaofeng Lu; Bin Huang; Rongjun Zhang; Xiaoshuang Han; Xuemei Yu; Weijian Zhang; Yanping Zhu; Dongfang Wang; et al. (Journal of Cleaner Production, 2025)

Effects of inorganic salt ions on long-term retrogradation characteristics of lotus seed starch under microwave treatment - Yingting Zhao; Zhiyang Lu; Yang Liu; Yanping Lei; Yuting Tian (Food Hydrocolloids, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Electron beam/persulfate-induced second-scale upcycling of wastewater polyvinyl alcohol with ultra-low chemical input - Tao Zhang; Yanping Zhu; Yongle Yu; Xiaoya Pan; Pan Zhao; Shihu Shu; Dongfang Wang; Jiping Shi; Li Liu; Weijian Zhang; Bin Huang; Xiaofeng Lu; et al. (Water Research, 2025)

Solvation–interface coupling strategy enables dendrite-free zinc anodes via amino acid-derived poly(ionic liquid) films - Kexuan Zang; Wenqi Song; YanPing Sun; Puang Lu; Sufeng Zhang; Zongchen Miao; Liwei Qian; Valentin Nica; Mohaned Hammad (Chemical Engineering Journal, 2025)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

Synthesizing ZIF-8 functionalized biochar by in situ reuse of residual Zn from chemical activation for enhanced tetracycline hydrochloride adsorption removal - Jianying Liu; Qian Zeng; Yao Chen; Zhongde Dai; Wenju Jiang; Lu Yao; Junfeng Zheng; Dengrong Sun; Yanping Wu; Lin Yang (Journal of Environmental Chemical Engineering, 2025)

Influence of tin doping on the activity and mechanism of CeO2 catalyst for selective catalytic reduction of NO with NH3 - Jingsong Zhou; Yanping Du; Yuqing Qiao; Fei Zhou; Zhou Liu; Zhibo Xiong; Mengqi Liu; Wei Lu (Journal of Environmental Chemical Engineering, 2025)

W2O6/CoFe2O4: An efficient catalyst to activate peroxymonosulfate for the elimination of antibiotic-resistant bacteria and genes in aquaculture effluent - Yanqiong Zhang; Muting Yan; Gaoling Wei; Fengru Lu; Feng Li; Peng Liu; Yanping Zhu; Han Gong (Journal of Environmental Chemical Engineering, 2025)

Topping-induced transcriptome changes reveal PaSPL-mediated regulation of plant architecture in Platanus acerifolia - Yanping Zhang; Yali Guan; Yongkang Lu; Lin Wang; Yuqing Chen; Manzhu Bao (Plant Molecular Biology, 2025)

Montmorillonite-enhanced Carboxymethylcellulose/Polyethyleneimine aerogel: A highly efficient and reusable adsorbent for caffeine removal from tea infusions - Wenyue Yu; Yangyu Zhou; Ya Liu; Huan Guo; Lihui Huang; Lu Feng; Jinrong Bai; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Food Chemistry, 2025)

Paracoccus yibinensis sp. nov., a novel bacterium with astaxanthin producing isolated from the environment of Chinese distilled Baijiu - Qingchun Luo; Yanping Lu; Xi Li; Jian Su; Pengju Zhao; Zhu Zhang; Yang Gu; Dong Zhao; Jia Zheng (Antonie van Leeuwenhoek, 2025)

WD40 proteins PaTTG1 interact with both bHLH and MYB to regulate trichome formation and anthocyanin biosynthesis in Platanus acerifolia - Qi Mengxuan; Tian Xinyue; Chen Yuqing; Lu Yongkang; Zhang Yanping (Plant Science, 2025)

Birnessite enhanced Cr(III) oxidation during subsurface geochemical processes: Role of Mn(III)-induced nonphotochemical reactive oxygen species - Yuting Zhou; Chuling Guo; Yanping Deng; Yanjun Jiang; Meiling Yin; Kai Chen; Siyu Zhang; Guining Lu; Zhi Dang (Environmental Pollution, 2025)

Fluorinated Zn-porphyrin covalent organic frameworks with optimized hydrophobic/hydrophilic balance towards stable Zn anodes - Xia Li; Yanping Chu; Shouliang Lu; Liangdan Chen; Long Su; Fei Lu; Zhen Chen; Xinpei Gao (Chemical Engineering Journal, 2025)

Mass mortality associated with carpione rhabdovirus in golden pompano (Trachinotus ovatus) in China: First report - Heng Sun; Jie Huang; Haoyu Wang; Yule Zhang; Qing Fei; Jie Zhou; Lindi Yang; Yanping Li; Jichang Jian; Yishan Lu; Shuanghu Cai; Yucong Huang (Aquaculture, 2025)

Bisulfite-free detection of DNA methylation in early-stage lung cancer with a multiplex SERS immunoassay - Dechan Lu; Yanping Chen; Longfeng Ke; Zufang Huang; Yudong Lu; Jing Wang (Chemical Engineering Journal, 2025)

Integrating network pharmacology and experimental verification to explore the pharmacological mechanisms of phlorizin against osteoarthritis - Yi Yao; Qiuling Zhong; Yanping Zhong; Zixin Gao; Bo Zhou; Chun Lu; Li Zheng; Feiying Yin; Manli Tan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Fusarium oxysporum causes the root rot disease of Polygonatum cyrtonema in China - Jiuchun An; Lu Luo; Xiaohong Ou; Yanping Gao; Lanping Guo; Chenghong Xiao; Weike Jiang; Tao Zhou; Qing-Song Yuan (Crop Protection, 2024)

Unveiling the impact of exposed mineral facets on chromium repartitioning in aging lepidocrocite - Xiaofei Li; Chuling Guo; Xiaohu Jin; Qian Yao; Yanping Bao; Xueding Jiang; Guining Lu; Suresh C. Pillai; Hailong Wang; Zhi Dang (Science of The Total Environment, 2024)

Promotional effect of microwave radiation treatment on the desorption of CO2 from mono-ethanolamine (MEA) solution over FeOOH catalyst - Haoran Zhang; Junge Lv; Zhibo Xiong; Huancong Shi; Jing Jin; Mengqi Liu; Yanping Du; Wei Lu (Journal of Environmental Chemical Engineering, 2024)

Construction of structure-matching In-Ni catalysts for the selective hydrogenation of α-methylacrolein - Lin Ai; Yanping Chen; Fang Lu; Jiaxu Liu; Xiao-Feng Wu; Shengjun Huang (Chemical Engineering Journal, 2024)

Hexagonal liquid crystals as emerging quasi solid-state electrolytes for aqueous lithium-ion batteries - Weirong Ren; Zhaowei Hou; Long Su; Xinpei Gao; Yanping Chu; Liqiang Zheng; Fei Lu (Chemical Engineering Journal, 2024)

Transcriptome analysis reveals the importance of phototransduction during the first-feeding in mandarin fish (Siniperca chuatsi) - Ke Lu; Jiaqi Wu; Shulin Tang; Di Peng; Asma Bibi; Liyun Ding; Yanping Zhang; Xu-Fang Liang (Functional & Integrative Genomics, 2024)

Rapid redox-response featured visual ascorbic acid sensor based on simple-assembled europium metal-organic framework - Lin-Lin Zhang; Li Li; Dan Wang; Yanping Hong; Kaijie Tang; Jiaxin Hong; Zeng Chen; Wuying Yang; Limin Lu; Lu-Ying Duan (Food Chemistry, 2024)

ChCaspase-1 cleaves ChGasdermin-E, inducing pyroptosis, and participates in the bacterial defence of the oyster Crassostrea hongkongensis - Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Ruwen Yang; Shu Xiao; Fan Mao; Yanping Qin; Haitao Ma; Yuehuan Zhang; Yang Zhang; ZiniuYu; et al. (Aquaculture, 2024)

Effect of biochar-derived DOM on contrasting redistribution of chromate during Schwertmannite dissolution and recrystallization - Xiaofei Li; Tianfu Li; Paramsothy Jeyakumar; Jiayi Li; Yanping Bao; Xiaohu Jin; Jun Zhang; Chuling Guo; Xueding Jiang; Guining Lu; Zhi Dang; Hailong Wang (Journal of Hazardous Materials, 2024)

Spatial heterogeneity and driving mechanisms of carbon storage in the urban agglomeration within complex terrain: Multi-scale analyses under localized SSP-RCP narratives - Hongyi Zhang; Xin Li; Yanping Luo; Lu Chen; Minxi Wang (Sustainable Cities and Society, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Leaf morpho-anatomy and taxonomic significance in five Dendrobium sect. Stachyobium species from China - Yunxi Xie; Yanping Wang; Lei Tao; Wenhao Liu; Yan Luo; Lu Li (Flora, 2024)

Self-assembled multifunctional Prussian blue analogues nanocomposite for MRI-guided multimodal therapy for breast cancer - Min Zhang; Yanping Wu; Xingchen Lu; Yuhan Qin; Cong Zhang; Wenjie Gu; Ruochen Gao; Yuanyuan Qi; Meng Wang; Qingli Huang (Chemical Engineering Journal, 2024)

Phytoplankton community responses to the combined effects of internal waves and anticyclonic eddies shed from the Kuroshio intrusion - Yanping Zhong; Xiaolin Bai; Edward A. Laws; Wenfang Lu; Zhida Huang; Wupeng Xiao; Jixin Chen; Lingqi Ma; Xin Liu; Bangqin Huang (Ocean Dynamics, 2024)

SVEN_5003 is a Major Developmental Regulator in Streptomyces venezuelae - Yanping Zhu; Ting Lu; Hanlei Zhang; Meng Liu; Xiuhua Pang (Current Microbiology, 2024)

Influence of organic sulfur gas-phase sulfation on the NH3-SCR activity of CeO2 catalyst: The competitive adsorption and conversion of CS2 and COS at a low hydrolysis temperature - Zhibo Xiong; Zhenchang Sun; Jiaxing Liu; Yanping Du; Yafei Zhu; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Fuel, 2024)

Dual-Coordinated atomically dispersed Pt nanozymes evoke efficient pyroptosis for cancer immunotherapy - Jingqi Chen; Yanping Tang; Yan Lin; Xiuxin Lu; Lineng Wei; Shiyu Xia; Wenxin Niu; Weizhong Tang; Weiqing Zhang (Chemical Engineering Journal, 2024)

Online LC-ESI-MS/MS comparative analysis of N/O-glycopatterns in human colostrum from different ethnic groups in Northwest China - Xiaoqin Wang; Jing Liu; Shukai Wang; Yutao Xie; Yipei Liu; Jiangbo Fan; Yanping Li; Yu Lu; Linjuan Huang; Zhongfu Wang (Carbohydrate Polymers, 2024)

Promotional effect of H2O introduction on the NH3-SCR activity of the gas-phase sulfated CeO2 catalyst by organic CS2+COS: Influence of H2O concentration - Jiaxing Liu; Yafei Zhu; Zhenchang Sun; Yanping Du; Zhibo Xiong; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Journal of Environmental Chemical Engineering, 2023)

Precise diagnosis of breast phyllodes tumors using Raman spectroscopy: Biochemical fingerprint, tumor metabolism and possible mechanism - Yifan Wu; Yaohui Wang; Chang He; Yan Wang; Jiayi Ma; Yanping Lin; Liheng Zhou; Shuguang Xu; Yumei Ye; Wenjin Yin; Jian Ye; Jingsong Lu (Analytica Chimica Acta, 2023)

Drought characteristics and dominant factors across China: Insights from high-resolution daily SPEI dataset between 1979 and 2018 - Lingling Wan; Virgílio A. Bento; Yanping Qu; Jianxiu Qiu; Hongquan Song; RongRong Zhang; Xiaoping Wu; Feng Xu; Jinkuo Lu; Qianfeng Wang (Science of The Total Environment, 2023)

Manipulating critical memory periods to treat psychiatry disorders - Jiahui Deng; Xiao Lin; Yongbo Zheng; Sizhen Su; Xiaoxing Liu; Kai Yuan; Le Shi; Yanping Bao; Lin Lu (Science Bulletin, 2023)

Extraction of rubidium and cesium from oilfield brine by the two-step adsorption–flotation method - Dezhen Fang; Miao Lu; Yanping Wang; Liang Ma; Kexin Li; Haining Liu; Huifang Zhang; Guosheng Shi; Zhijian Wu; Xiushen Ye (Minerals Engineering, 2023)

Causal relationships between chronotype and risk of multiple cancers by using longitudinal data and Mendelian randomization analysis - Shanshan Tian; Longtao Huangfu; Sizhi Ai; Junwei Zheng; Le Shi; Wei Yan; Ximei Zhu; Qianwen Wang; Jiahui Deng; Yanping Bao; Suhua Chang; Lin Lu (Science China Life Sciences, 2023)

Comparative Analysis of the Expression of Resistance-Related Genes Respond to the Diversity Foliar Pathogens of Pseudostellaria heterophylla - Xiao-Ai Wang; Yanping Gao; Weike Jiang; Lu Wang; Hui Wang; Xiaohong Ou; Yang Yang; Honglin Wu; Lanping Guo; Tao Zhou; Qing-Song Yuan (Current Microbiology, 2023)

Bridging the gap between artificial intelligence and mental health - Tangsheng Lu; Xiaoxing Liu; Jie Sun; Yanping Bao; Björn W. Schuller; Ying Han; Lin Lu (Science Bulletin, 2023)

China Brain Project: from bench to bedside - Xiaoxing Liu; Teng Gao; Tangsheng Lu; Yanping Bao; Gunter Schumann; Lin Lu (Science Bulletin, 2023)

Microbial reduction of schwertmannite by co-cultured iron- and sulfate-reducing bacteria - Changdong Ke; Chuling Guo; Siyu Zhang; Yanping Deng; Xiaofei Li; Yuancheng Li; Guining Lu; Fei Ling; Zhi Dang (Science of The Total Environment, 2023)

A magnetic adsorbent with metal-organic framework based on ammonium phosphomolybdenum heteropoly tungstate (AWP): Selective adsorption of Rb+ and Cs+ from aqueous resources and stripping with ammonium salts - Yanping Wang; Kexin Li; Liang Ma; Dezhen Fang; Miao Lu; Xiushen Ye; Haining Liu; Huifang Zhang; Xiaoli Tan; Zhijian Wu (Hydrometallurgy, 2023)

Photocatalytic and oxidation mechanisms of Fe–Ag@AgCl: Effect on co-existing arsenic (III) and Escherichia coli - Yanping Cui; Qian Ye; Haili Wang; Xuewen Duo; Liang Peng; Wei Dong; Xiaoxiao Cui; Yue Lu; Yajie Li (Environmental Research, 2023)

Cu doping and Ti3C2OH quantum dots co-modifications of Zn3In2S6 boosted photocatalytic reduction of CO2 to CO via accelerating carriers transfer and enhancing CO2 adsorption and activation - Jinhang Yang; Yanping Hou; Jiangli Sun; Ting Liang; Tingting Zhu; Jiaxiang Liang; Xiaoqiong Lu; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Occurrence of polycyclic aromatic hydrocarbons (PAHs) in the seafood from an important fishing area in the East China Sea and a comparison between seafood from different origins - Wang Qian; Lu Dequan; Xiong Yiran; Peng Fei; Li Juan-ying; Wu Feng; Chu Yanping; Sun Ruihua; Tian Siquan (Environmental Monitoring and Assessment, 2022)

HrreNet: semantic segmentation network for moderate and high-resolution satellite images - Yanping Li; Lu Wang; Lei Zhang; Haiwen Chen; Shiying Wang; Xiaoying Wang (International Journal of Remote Sensing, 2022)

Jasmonate increases terpene synthase expression, leading to strawberry resistance to Botrytis cinerea infection - Zibo Zhang; Suwen Lu; Wenbin Yu; Sadeghnezhad Ehsan; Yanping Zhang; Haifeng Jia; Jinggui Fang (Plant Cell Reports, 2022)

Molecular epidemiology and clinical characterization of human rhinoviruses circulating in Shanghai, 2012-2020 - Haixia Jiang; Tianyun Yang; Chunyi Yang; Yanping Lu; Zhigang Yi; Qin Zhang; Wei Wang (Archives of Virology, 2022)

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Impact of MtrA on phosphate metabolism genes and the response to altered phosphate conditions in Streptomyces - Yanping Zhu; Peipei Zhang; Ting Lu; Xinyuan Wang; Aiying Li; Yinhua Lu; Meifeng Tao; Xiuhua Pang (Environmental Microbiology, 2021)
Summary Phosphate metabolism is known to be regulated by the PhoPR regulatory system in Streptomyces and some other bacteria. In this study, we report that MtrA also regulates phosphate metabolism in Streptomyces . Our data showed that, in Streptomyces coelicolor , MtrA regulates not only phosphate metabolism genes such as phoA but also phoP under different phosphate conditions, including growth on rich complex media without added inorganic phosphate and on defined media with low or high concentrations of inorganic phosphate. Cross‐regulation was also observed among mtrA , phoP and glnR under these conditions. We demonstrated both in vitro and in vivo binding of MtrA to the promoter regions of genes associated with phosphate metabolism and to the intergenic region between phoR and phoU , indicating that these phosphate metabolism genes are targets of MtrA. We further showed that MtrA in S . lividans and S . venezuelae has detectable regulatory effects on expression of phosphate metabolism genes. Additionally, the MtrA homologue from Corynebacterium glutamicum bound predicted MtrA sites of multiple phosphate metabolism genes, implying its potential for regulating phosphate metabolism in this species. Overall, our findings support MtrA as a major regulator for phosphate metabolism in Streptomyces and also potentially in other actinobacteria.

GAS5 knockdown suppresses inflammation and oxidative stress induced by oxidized low-density lipoprotein in macrophages by sponging miR-135a - Yunyan Zhang; Xianben Lu; Minjun Yang; Jiaolin Shangguan; Yanping Yin (Molecular and Cellular Biochemistry, 2021)

Sulfate-reducing bacterial community shifts in response to acid mine drainage in the sediment of the Hengshi watershed, South China - Yanping Bao; Xiaohu Jin; Chuling Guo; Guining Lu; Zhi Dang (Environmental Science and Pollution Research, 2021)

Formulation and Pharmacokinetic Evaluation of a Drug-in-Adhesive Patch for Transdermal Delivery of Koumine - Yanping Su; Wenxiang Lu; Xiaoling Fu; Ying Xu; Lixiang Ye; Jian Yang; Huihui Huang; Changxi Yu (AAPS PharmSciTech, 2020)

First Case of Rhinocerebral Mucormycosis Caused by Lichtheimia ornata, with a Review of Lichtheimia Infections - Junling Pan; Clement Tsui; Mengxing Li; Kun Xiao; G. Sybren de Hoog; Paul E. Verweij; Yu Cao; Hongguang Lu; Yanping Jiang (Mycopathologia, 2020)

New Perspectives from Misdiagnosis: A Case of Primary Cutaneous Cryptococcosis Treated with Hydroxychloroquine Sulfate Successfully - Wanglan Luo; Di Che; Hongguang Lu; Yanping Jiang (Mycopathologia, 2020)

From the Pharynx to the Brain: A Case of Rapidly Progressing Mucormycosis - Yanping Jiang; Hongguang Lu (Mycopathologia, 2019)

Beraprost sodium mitigates renal interstitial fibrosis through repairing renal microvessels - Shulin Li; Yanping Wang; Lu Chen; Zhuojun Wang; Guodong Liu; Bangjie Zuo; Caixia Liu; Dong Sun (Journal of Molecular Medicine, 2019)

Genetic diversity and pathogenicity dynamics of Magnaporthe oryzae in the Wuling Mountain area of China - Xin Xu; Wu Yang; Ke Tian; Jie Zheng; Xinqiong Liu; Kai Li; Wei Lu; Yanping Tan; Yonghua Qin; Chuntai Wang (European Journal of Plant Pathology, 2019)

Dioxin-like polychlorinated biphenyls in marine fish from Shandong, China, and human dietary exposure - Yanping Cao; Dafeng Jiang; Fenghua Li; Jindong Chen; Wei Li; Yanni Jiao; Lu Li (Food Additives & Contaminants Part B-Surveillance, 2018)

Bmi1 Regulates the Proliferation of Cochlear Supporting Cells Via the Canonical Wnt Signaling Pathway - Xiaoling Lu; Shan Sun; Jieyu Qi; Wenyan Li; Liman Liu; Yanping Zhang; Yan Chen; Shasha Zhang; Lei Wang; Dengshun Miao; Renjie Chai; Huawei Li (Molecular Neurobiology, 2017)

Cycloartane-type triterpenoids from Astragalus hoantchy French. - Kai Guo; Xiaofeng He; Dengxue Lu; Yanping Zhang; Xiuzhuang Li; Zhiqiang Yan; Bo Qin (Natural Product Research, 2017)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

Preparation of highly purified timosaponin AIII from rhizoma anemarrhenae through an enzymatic method combined with preparative liquid chromatography - Lu Lu; Yanping Liu; Yue Ding; Jianwei Hou; Yong Zhang; Haiping Xue; Tong Zhang (Natural Product Research, 2016)

The Concept of Ecthyma Gangrenosum Illustrated by a Fusarium oxysporum Infection in an Immunocompetent Individual - Yanping Jiang; Abdullah M. S. Al-Hatmi; Yining Xiang; Yu Cao; Albert H. G. Gerrits van den Ende; Ilse Curfs-Breuker; Jacques F. Meis; Hongguang Lu; G. Sybren de Hoog (Mycopathologia, 2016)

A single mutation in the PBC loop of VP2 is involved in the in vitro replication of infectious bursal disease virus - Xiaole Qi; Xiang Gao; Zhen Lu; Lizhou Zhang; Yongqiang Wang; Li Gao; Yulong Gao; Kai Li; Honglei Gao; Changjun Liu; Hongyu Cui; Yanping Zhang; et al. (Science China Life Sciences, 2016)

A cluster of 3′ coterminal transcripts from US12–US17 locus of human cytomegalovirus - Ying Lu; Yanping Ma; Zhongyang Liu; Liying Han; Shuang Gao; Bo Zheng; Chang Liu; Ying Qi; Zhengrong Sun; Yujing Huang; Qiang Ruan (Virus Genes, 2016)

QTL mapping for flowering time in different latitude in soybean - Sijia Lu; Ying Li; Jialin Wang; Peerasak Srinives; Haiyang Nan; Dong Cao; Yanping Wang; Jinliang Li; Xiaoming Li; Chao Fang; Xinyi Shi; Xiaohui Yuan; et al. (Euphytica, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

Brain differences in first-episode schizophrenia treated with quetiapine: a deformation-based morphometric study - Chunlan Yang; Shuicai Wu; Wangsheng Lu; Yanping Bai; Hongjian Gao (Psychopharmacology, 2015)

Effects of hydrogen peroxide accumulation, lipid peroxidation, and polyphenol oxidation during superficial scald development in ‘Fuji’ apples - Xingang Lu; Yanping Ma; Xinghua Liu (Horticulture, Environment, and Biotechnology, 2014)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

Reference gene selection for qPCR in Ammopiptanthus mongolicus under abiotic stresses and expression analysis of seven ROS-scavenging enzyme genes - Jing Shi; Meiqin Liu; Junna Shi; Guangshun Zheng; Yanping Wang; Jinyu Wang; Yuzhen Chen; Cunfu Lu; Weilun Yin (Plant Cell Reports, 2012)

Genetic variation in the GCKR gene is associated with non-alcoholic fatty liver disease in Chinese people - Zhen Yang; Jie Wen; Xiaoming Tao; Bin Lu; Yanping Du; Mei Wang; Xuanchun Wang; Weiwei Zhang; Wei Gong; Charlotte Ling; Songhua Wu; Renming Hu (Molecular Biology Reports, 2011)

Brief report: a new profile of terminal N-acetyllactosamines glycans on pig red blood cells and different expression of α-galactose on Sika deer red blood cells and nucleated cells - Yingxia Tan; Feng Gong; Subo Li; Shouping Ji; Yanping Lu; Hongwei Gao; Hua Xu; Yangpei Zhang (Glycoconjugate Journal, 2010)

Human cytomegalovirus UL145 gene is highly conserved among clinical strains - Zhengrong Sun; Ying Lu; Qiang Ruan; Yaohua Ji; Rong He; Ying Qi; Yanping Ma; Yujing Huang (Journal of Biosciences, 2007)